Nymphomania pada Tokoh Yuriko Hirata dalam Novel Grotesque Karya Natsuo Kirino - Puri Nur Cahya, Ni Ketut (Humanis, 2017)
This study is entitled "Nymphomania on the character of Yuriko Hirata in Novel Grotesque by Natsuo Kirino". This study aims to understand the causes and behaviors of Nymphomania of Yuriko Hirata. The theory used in this research is theory of literary psychology by Endaswara (2003) and using psychoanalytical theory by Freud (1980). This research is also using nymphomania concept from Kartini Kartono to find out the causes and the behavior of nymphomania of Yuriko Hirata. This study found four causes of nymphomania in Yuriko Hirata: 1) no peace in family; 2) domestic violence; 3) desire to be adored; 4) revenge against the father figure. Having known the cause, this research also found four nymphomania behaviors in Yuriko Hirata: 1) have a high sexual desire; 2) want to have more than one lover; 3) have a free sex behavior; and 4) have a adultery behavior. The result of the analysis shows that Yuriko is dominated by id. Yuriko's ego is dependent on the id so that the sexual desires of  Yuriko can’t be controlled by the ego or superego.